Political Institutions and Growth Collapses - Ugo Panizza; Alejandro Gaviria; Ernesto H. Stein; Jessica Seddon Wallack (Inter-American Development Bank, Research Department, 2000)
This paper tests whether Rodrik`s (1999) results that institutions for conflict management are associated with the ability to react to economic shocks are robust to different ways of defining the quality of such institutions. We measure the quality of conflict management institutions with two different indices. The first is an index of political constraints on the ability of the executive to impose its will. These constraints limit the ability of the government to arbitrarily change the rules of the game and therefore may reduce redistributive struggles. The second index measures the degree of political particularism. We define political particularism as the policymakers` ability to further their career by catering to narrow interests rather than broader national platforms. The indices used in this paper solve the endogeneity and subjectivity biases that affect Rodrik`s measure of institutional quality. We find strong support for the idea that high levels of political constraints and intermediate levels of political particularism are associated with a quick recovery from economic shocks.
Keywords: 330; Wirtschaftswachstum; Wirtschaftskrise; Institutionalismus; Sozialer Konflikt; Entwicklungsländer; Schwellenländer